Prognozowanie wpływu zmian klimatycznych na dynamikę drzewostanów bukowych w polskiej i ukraińskiej części Roztocza - Kozak, Ihor; Kozak, Hanna; Parpan, Taras; Typiak, Barbara (Leśne Prace Badawcze, 2017)
This study has been carried out in the Polish Roztoczański National Park and the Ukrainian Ravs’ke Roztochia Regional Landscape Park, both of which are part of the Roztoche region. In each of these two locations, representative study plots were established in beech ( Fagus sylvatica L.) stands occupying sites with similar environmental conditions. A longterm prognosis for the dynamics of the chosen beech stands were generated using the computer model FORKOME. The model was used to forecast stand developments for four climatic scenarios (warm-humid, warm-dry, cold-humid, cold-dry) covering a time span of 500 years. Our simulation results indicate that in the control scenario, beech stands were dominating and cyclical changes between beech and Silver fir ( Abies alba Mill.) may occur. In the scenarios with assumed climate warming, a decline of fir biomass and an increase of beech biomass, as compared to the control conditions, was noticed. In the scenario with assumed climate cooling, fir biomass increased for the duration of the investigated time span. To conclude, the application of the FORKOME model was found to be a useful tool for analyzing potential scenarios of long-term dynamics of beech stands in the Roztoche region in Poland and Ukraine.